1984
DOI: 10.1271/bbb1961.48.1753
|View full text |Cite
|
Sign up to set email alerts
|

Shoyu (soy sauce) flavor components: Neutral fraction.

Abstract: Fromthe vacuumdistilled volatiles ofshoyu, a neutral fraction was obtained. Shoyu was also directly extracted with dichloromethane and then the extract was separated into ten (A~J) fractions. The J fraction was a neutral one. The J fraction was further separated into twelve fractions by liquid column chromatography. All fractions obtained were analyzed by gas chromatography and combined gas chromatography-mass spectrometry. Consequently, 142 components were identified, 82 of which have not been reported previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…Nevertheless, the typical compound of soy sauce, 4-EG, and 4-EP, were not found in aHVP sample. 2-methoxy-phenol, typically described as smoky, spicy, and medicine-like (Nunomura et al 1984;Kaneko et al 2012Kaneko et al , 2013, was detected in all samples, while phenol was not found in pure soy sauce sample. By calculation, it was clear that the total amount of phenols in pure soy sauce sample was not high and phenols accounted for a little part of volatile flavor compounds.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Nevertheless, the typical compound of soy sauce, 4-EG, and 4-EP, were not found in aHVP sample. 2-methoxy-phenol, typically described as smoky, spicy, and medicine-like (Nunomura et al 1984;Kaneko et al 2012Kaneko et al , 2013, was detected in all samples, while phenol was not found in pure soy sauce sample. By calculation, it was clear that the total amount of phenols in pure soy sauce sample was not high and phenols accounted for a little part of volatile flavor compounds.…”
Section: Resultsmentioning
confidence: 82%
“…Among these compounds, dozens of components were shared commonly with different amount in soy sauce products. According to the previous report (Nunomura et al 1984;Kaneko et al 2012Kaneko et al , 2013Feng et al 2015), some typical or key volatile flavor compounds, which might be the contributors to the flavor of soy sauce, were summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main steps in flavour development in soy sauce production are heat treatment of raw materials, koji culturing and the mash fermentation 31 . There have been a few studies conducted to determine the volatile compounds in soy sauces produced in different Asian countries or regions 1,16,19,21,26,31 . For example, Nunomura and co-authors [19][20][21] investigated the volatile compounds of Japanese soy sauce using a combination of vacuum distillation-solvent distillation and gas chromatography-mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%